Association of all forms of malnutrition and socioeconomic status, educational level and ethnicity in Colombian children and non-pregnant women (2020)
ABSTRACT: Objective: To examine the association of all forms of malnutrition and socioeconomic status (SES), educational level and ethnicity in children <5 years, nonpregnant adolescent women (11–19 years) and non-pregnant adult women (20–49 years) in Colombia. Design: Cross-sectional analysis of data from the 2010 Colombian National Nutrition Survey. The prevalence of malnutrition was compared across categories of SES, educational level and ethnicity. Setting: Colombia. Participants: The sample for the current analysis comprised children <5 years, non-pregnant adolescent women (11–19 years) and non-pregnant adult women (20–49 years). Results: In children <5 years, a low SES and maternal educational level were significantly associated with a lower prevalence of overweight/obesity compared with high levels of SES and maternal education, that is, the prevalence of overweight/obesity was 1·4 and 1·6 times lower in categories of low SES and educational levels, respectively. In contrast, the prevalence of wasting, stunting and anaemia was higher in the lowest SES and maternal educational categories (the prevalence was between 1·1 and 1·8 times higher for these indicators). In women, the lowest SES (11 and 19 years) and educational levels (20 and 49 years) exhibited a higher prevalence in all forms of malnutrition compared with their counterparts in the highest categories (i.e. overweight/obesity, stunting and anaemia). Additionally, indigenous or Afro-Colombian children and women had the highest prevalence of malnutrition in comparison with other ethnicities. Conclusions: These results suggest that public policies should address all forms of malnutrition that occur in the most vulnerable populations in Colombia using multiple strategies.